Microbial communities associated with the skin, gill, and gut of large yellow croaker (Larimichthys crocea) - Jingan Wang; Chenghao Hu; Xiaojie Tong; Yuan Gao; Renjie Liang; Chibo Liu; Kai Zhao (BMC Microbiology)
Abstract The microbiota inhabiting the surface of fish mucosal tissue play important roles in the nutrition, metabolism and immune system of their host. However, most investigations on microbial symbionts have focused on the fish gut, but the microbiota associated with external mucosal tissues (such as the skin and gill) is poorly understood. This study characterised the traits and dynamic of microbial communities associated with the skin, gill and gut of large yellow croaker (Larimichthys crocea) culturing with net enclosures or pens at different sampling times (with seasonal transition). Results revealed the structure and function of microbial communities differed according to the mucosal tissues of large yellow croaker. The richness and diversity of microbiota in the skin were significantly higher than that in the gill and gut. Discriminative microbial taxa such as Psychrobacter in the skin, Enterobacterales in the gill, and Fusobacterium in the gut, and discriminative predictive functions were identified in the skin, gill and gut. Furthermore, different environmental-related factors (such as sampling time/season and culture method) had impacts on the fish microbiota differently. The diversity and composition of microbiota associated with the skin, gill and gut changed over time, and the difference in skin microbiota across sampling times was most significant among the three tissues. The culture method significantly impacted the diversity and composition of skin microbiota, but no significant difference was found in the gill and gut microbiota between net enclosure and net pen. These results indicated that the skin microbiota of large yellow croaker was more diverse and affected by environmental-related factors than other tissues. This study provides new insights into the structure, environmental response pattern, and relationship with host health of microbiota associated with the mucosal tissues of large yellow croaker.